2021
DOI: 10.2174/1381612826666201002145454
|View full text |Cite
|
Sign up to set email alerts
|

Combining Angiogenesis Inhibitors with Radiation: Advances and Challenges in Cancer Treatment

Abstract: Background: Radiation therapy is a widely employed modality which is used to destroy cancer cells, but it also tends to induce changes in the tumor microenvironment and promote angiogenesis. Radiation when used as a sole means of therapeutic approach to treat cancer, tends to trigger the angiogenic pathways, leading to the upregulation of several angiogenic growth factors such as VEGF, bFGF, PDGF and angiogenin. This uncontrolled angiogenesis leads to certain angiogenic disorders like vascular outgrowth and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 100 publications
0
9
0
3
Order By: Relevance
“…These factors are associated with degradation of the extracellular matrix and the advancement of tumor metastasis and angiogenesis 42 . In vascular endothelial cells, miR‐3529‐3p downregulated the expression of VEGF and bFGF, which not only stimulate vascular permeability, but also trigger the migration of endothelial cells 43 . Considering the antiangiogenic role of miR‐3529‐3p in cells, we also assessed neovascularization in a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are associated with degradation of the extracellular matrix and the advancement of tumor metastasis and angiogenesis 42 . In vascular endothelial cells, miR‐3529‐3p downregulated the expression of VEGF and bFGF, which not only stimulate vascular permeability, but also trigger the migration of endothelial cells 43 . Considering the antiangiogenic role of miR‐3529‐3p in cells, we also assessed neovascularization in a xenograft model.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of anti-angiogenic therapy with other therapies, including chemotherapy, radiotherapy, immunotherapy and anti-EGFR therapy, has good efficacy due to the vaso-normalization effect induced by anti-angiogenic agents (Tian et al 2020 ). Radiation alone as the sole means of treating cancer often triggers the angiogenesis pathway, leading to upregulation of multiple angiogenic growth factors, and anti-angiogenic inhibitors can help overcome this fact (Rani and Prabhu 2021 ). Randomized Phase III studies have also shown that treatment with antiangiogenic agents in combination with programmed cell death ligand 1 (PD-L1) antibodies significantly improves survival compared with standard therapy in renal cell carcinoma (RCC), NSCLC and hepatocellular carcinoma (HCC) (Hack et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combination of anti-angiogenic therapy with other therapies, including chemotherapy, radiotherapy, immunotherapy and anti-epidermal growth factor receptor (EGFR) therapy, has good e cacy due to the vasonormalization effect induced by anti-angiogenic agents 31 . Radiation alone as the sole means of treating cancer often triggers the angiogenesis pathway, leading to upregulation of multiple angiogenic growth factors, and anti-angiogenic inhibitors can help overcome this fact 32 . Randomized Phase III studies have also shown that treatment with antiangiogenic agents in combination with PD-L1 antibodies signi cantly improves survival compared with standard therapy in RCC, NSCLC and HCC.…”
Section: Discussionmentioning
confidence: 99%